Employability and 'Marginal Efficiency' of Labour in Post-COVID Economy. Issue 1 (June 2022) - Irshad, S. Mohammed; Raj, Vimal
COVID-19-induced lockdown resulted into a differential impact and the most vulnerable among them are the labour. State is ineffective in preventing income and livelihood loss of the workers. Higher supply and lower wages resulted in a huge reserve labour force in developed and developing countries. The employer in a post-COVID economy is going to be highly selective and labour market also would be selective to labour. The labour is going to be free to move, however, the freedom of labour to move does not ensure better employability. This article explains about employability in the post-COVID economy.